Finite size effects on the structural and magnetic properties of sol-gel synthesized NiFe2O4 powders - George, M.; John, A. M.; Nair, S. S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2006)
Nanoparticles of nickel ferrite have been synthesized by the sol-gel method and the effect of grain size oil its structural and magnetic properties have been Studied in detail. X-ray diffraction (XRD) studies revealed that all the samples are single phasic possessing the inverse spinel structure. Grain size of the sol-gel synthesized powders has been determined from the XRD data and the strain graph. A grain size of 9 nm was observed for the as prepared powders of NiFe2O4 obtained through the sol-gel method. It was also observed that strain was induced during the firing process. Magnetization measurements have been carried out on all the samples prepared in the present series. It was found that the specific magnetization of the nanosized NiFe2O4 powders was lower than that of the corresponding coarse-grained counterparts and decreased with a decrease in grain size. The coercivity of the sol-gel synthesized NiFe2O4 nanoparticles attained a maximum value when the grain size was 15 nm and then decreased as the grain size was increased further. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: grain size; magnetic properties; Nanoparticles; Nickel ferrite; strain

On the magnetic and dielectric properties of nickel-neoprene nanoconaposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Chemistry and Physics, 2010)
Nickel nanocomposites were prepared by incorporating nickel nanoparticles in a neoprene matrix according to a specific recipe for various loadings of nickel particles. The dielectric properties of these composites were evaluated for different frequencies ranging from 100 kHz to 8 MHz at different temperatures from 30 degrees C to 120 degrees C. The dielectric permittivity increases with increase of nickel concentration. Increase in temperature enhances the permittivity initially, till 40 degrees C and thereafter the permittivity decreases. The dielectric loss exhibits relaxation peaks and the peaks shift to lower frequencies with increase in volume fraction of the nickel nanoparticles in the matrix. The evaluation of magnetic and dielectric properties of these composites suggests that the dielectric permittivity can be tailored by an appropriate loading of the filler using semi-empirical equations and the magnetic properties vary according to simple mixture equations. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Composite materials; dielectric properties; Elastomers; magnetic properties

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites